The Role of Virtual Teacher in the Digital Age: Engraver the Future of Indonesian Golden Generations - Sembiring, Maximus Gorky (Universitas Terbuka, 2022)
This study investigates the implications and complications of collective disruptive consequences on education, especially on the learning process. The driver of disruptions includes globalization and the Industrial Revolution 4.0 (including Society 5.0), demands for the Sustainable Development Goals, and the onslaught of the Covid-19 Pandemic. The results of the study are intended to broaden the horizons of virtual teachers in the digital era so that they are not hampered in carrying out their mandate due to the shift from offline to online learning. This study also aims to provide a basic overview for students and parents so as not to stutter suddenly as an implication of the shift in learning modes. Methodologically, this study uses a qualitative approach, specifically an integrative review. After going through four phases of the procedural process (Design, Implementation, Analysis, and Writing of Results and Review), this study succeeds in formulating four basic ideas for virtual teachers in the digital era. One: Ten characteristics of the virtual teacher of the digital age. Two: Self-transformation into a true virtual teacher according to the demands of 21st-century learning (cultural, functional, and digital transformation). Three: Proficient in three technical skills of virtual teachers to build Indonesia's golden generation (skills in developing interactive digital learning modules, packaging virtual-digital learning delivery, and compiling online learning assessments). Four: Mastering practical tips for becoming a virtual teacher (developing a golden generation, applying a growth mindset perspective) so that it is continuously adaptive to any kind of shift.